Japan : Financial Sector Assessment Program-Technical Note on Credit Intermediation. (IMF Staff Country Reports; Country Report ;, 2012)
This paper is an analysis of Japan's credit channel. The economic condition has no hindrance, but credit demand showed an inert performance. The state's policies have helped the flow of finance and prevent bankruptcy, but several other aspects act as an impediment to credit control. The Executive Board expects restructuring of financial policies in government-affiliated institutions, promotion of electronic registrations, risk-based financing, and reinforcing bank administrations. The Board takes up this paper as a study of Japan's thoughts in an efficient route to credit boom.